Addition of chromium propionate in dog food: metabolic, immunological, and oxidative effects - Farret M.H.* (2023)
© 2023 Informa UK Limited, trading as Taylor & Francis Group.Chromium is a trace element essential in metabolising carbohydrates, lipids, and proteins and is involved in other biological functions. Therefore, this study determined whether chromium propionate supplementation in dogs improves haematologic, metabolic, immune/inflammatory, and antioxidant biomarkers. A commercial product (Labex® Chromium) containing 0.4% chromium was used at 500 g/ton of food, which provided an additional calculated amount of 2 mg of chromium per kg of food. We used ten beagles divided into two treatments: the chromium group (supplemented with 0.380 mg of chromium/dog/day; T-CHR) and the control group comprised dogs fed a basal diet (no chromium supplementation). The experiment included two periods of 28 days, with an interval of 15 days, i.e. the dogs in the control group in the first period were in the chromium group in the second period (all dogs underwent all treatments in a crossover design). Dogs supplemented with chromium had higher serum mineral levels on days 14 and 28 (P ≤ 0.001). The group in the chromium group showed significantly higher numbers of total leukocytes and lymphocytes and concentrations of total protein, globulin, thio-proteins, and catalase activity in blood than the control group. Serum urea concentrations and TBARS (lipid peroxidation) were lower (P ≤ 0.05) in the chromium group. Tendencies towards lower concentrations of reactive oxygen species were observed on day 28 in the T-CHR group (P = 0.10). Chromium supplementation increased the concentration of cytokines in serum (tumour necrosis factor-alpha [TNF-α], IFN-γ, and IL-10) and C-reactive protein (P ≤ 0.05). Dogs in the chromium group had higher gamma globulin concentrations than controls (P ≤ 0.001). These findings suggest that supplementation with chromium propionate (2 mg/kg) in food positivity modulates metabolic, antioxidant, and immune indicators in dogs.